1997
DOI: 10.1007/bf01438312
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein expression in soft-tissue sarcomas

Abstract: Multidrug resistance (MDR) is an important problem in chemotherapy for neoplastic disease. In humans. MDR is mainly mediated by P-glycoprotein (P-gp) a product of the MDRI gene, which acts as a transmembrane protein pump and eliminates chemotherapeutic agents from the cells. Expression of P-gp was immunohistochemically studied by using two monoclonal antibodies, JSB-1 and C-219, on paraffin-embedded sections from 55 patients with soft-tissue sarcoma. The histological diagnosis of tumors was malignant fibrous h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Komdeur and colleagues found that MRP1 and lung resistance-related protein expression by immunohistochemistry was significantly higher in grades 2 and 3 STS, when compared with grade 1 (12) whereas Oda and colleagues detected a significant correlation between P-gp expression and the largest tumors (!5 cm) or high AJCC-staged tumors (13). In similar vein, Nakanishi and colleagues also documented that tumors expressing P-gp had a less favorable prognosis among high-or intermediate-grade STS in a series of 55 cases, some of which were treated with adjuvant chemotherapy (28). In synovial sarcoma, P-gp, and to a lesser extent MRP1, were not prognostic factors in a series of 54 cases (29).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Komdeur and colleagues found that MRP1 and lung resistance-related protein expression by immunohistochemistry was significantly higher in grades 2 and 3 STS, when compared with grade 1 (12) whereas Oda and colleagues detected a significant correlation between P-gp expression and the largest tumors (!5 cm) or high AJCC-staged tumors (13). In similar vein, Nakanishi and colleagues also documented that tumors expressing P-gp had a less favorable prognosis among high-or intermediate-grade STS in a series of 55 cases, some of which were treated with adjuvant chemotherapy (28). In synovial sarcoma, P-gp, and to a lesser extent MRP1, were not prognostic factors in a series of 54 cases (29).…”
Section: Discussionmentioning
confidence: 87%
“…The most plausible mechanism underlying the poor prognosis of ABCC1/MRP1 is related to its ability to remove diverse xenobiotics from the cell, including anticancer drugs. Besides this, some authors have found that MDR expression, at protein and/or RNA level, correlated with high grade (12,13,28) or stage III/IV (13) in STS. This is something that is not possible to test in our series, because only highest grade (G3 according FNLCC) and stage III were included.…”
Section: Discussionmentioning
confidence: 92%
“…Various mechanisms are involved in clinical drug resistance, but best studied is overexpression of MDR proteins, which leads to decreased intracellular accumulation of cytotoxic drugs. Score\group I II III IV I II III IV I II III IV 0 2 3 7 1 2 5 10 1 1 3 16 4 1 0 0 1 0 0 0 0 0 0 0 0 0 2 1 1 1 1 1 0 1 0 0 1 2 0 3 1 1 5 2 0 0 3 2 3 1 1 1 4 2 1 10 3 3 1 10 4 2 1 MDR protein expression has been studied in various primary paediatric solid tumours (3,17,18,20,(30)(31)(32)(33)(34)(35). De Cremoux et al investigated the clinical significance of mRNA expression level of MDR-associated genes in 29 advanced neuroblastoma samples and showed that P-gp and MRP1 mRNA overexpression was present in 74 and 30% of cases, respectively (31).…”
Section: Discussionmentioning
confidence: 99%
“…Synovial sarcoma RT-PCR Poor prognosis (7) , high proliferative rate (8) PAX3-FKHR Alveolar RMS RT-PCR Poor prognosis (2) Tumor-suppressor genes p53 and MDM2 coexpression Mixed STS IHC Poor prognosis (9) Dedifferentiated LS IHC Dedifferentiation (10) p53 Mixed STS IHC Poor prognosis (11) Mixed STS Mutation Poor prognosis (12) Leiomyosarcoma IHC, mutation Poor prognosis in deep tumor (13) Synovial sarcoma IHC Poor prognosis (14) Myxoid/round cell LS IHC Poor prognosis (15) Myxoid/round cell LS IHC, mutation High histological grade, poor prognosis (16) ES/PNET IHC Poor prognosis (17) DFSP Mutation Malignant transformation to fibrosarcoma (18) MDM2 mRNA Mixed STS qRT-PCR Poor prognosis (19) p16 INK4a Leiomyosarcoma IHC Poor prognosis (20) p14 ARF Myxoid/round cell LS IHC Poor prognosis (16) RB Dedifferentiated LS IHC, LOH, mutation Dedifferentiation (21) DAP kinase, p53 Leiomyosarcoma MSP, mutation High histological grade, poor prognosis (22) RASSF1A Mixed STS MSP Poor prognosis, frequent in leiomyosarcoma (23) Cell cycle regulators CHFR MPNST IHC Poor prognosis (24) p21 WAF1 Myxofibrosarcoma IHC High histological grade, poor prognosis (25) Growth factors and receptors EGFR Mixed STS IHC Poor prognosis (26) HGF/MET coexpression Synovial sarcoma IHC Poor prognosis (27) Multidrug resistance P-glycoprotein Mixed STS IHC Poor prognosis (28) Mixed STS IHC Poor response to chemotherapy (29) Mixed STS IHC Large tumor size, high stage (30) MDR1/MRP1, coexpression…”
Section: Ss18-ssx1mentioning
confidence: 99%
“…Several investigators have demonstrated that overexpression of P-gp is associated with poor prognosis in several kinds of STS, (28) as well as with poor pathological response to chemotherapy. (29) Coexpression of MDR1 and MRP1 mRNA was significantly correlated with tumor grade in STS.…”
Section: Multidrug Resistancementioning
confidence: 99%